ANALISIS BREAK EVEN POINT PADA USAHA SUSU KEDELAI “SOYKHU” - Dwiyan Raynata; Sufiyati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2026)
As public awareness of healthy lifestyle increases, demand for plant-based dairy products such as soy milk continues to rise due to its various advantages. The